2010
DOI: 10.1111/j.1525-1594.2010.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Liver Organoids in the Omentum and Kidney

Abstract: Liver organoids were reconstructed by mouse-immortalized hepatocytes and nonparenchymal cells (sinusoidal endothelial cells and hepatic stellate cells) in a radial-flow bioreactor (RFB). A biodegradable apatite-fiber scaffold (AFS) was used as a scaffold packed in the RFB, which enables three-dimensional cell cultures. The organoids cocultured in the RFB showed a liver-like structure with high-density layers of hepatocytes and the formation of vessel-like structures. A liver organoid consisting of three cocult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…When hepatocytes mixed in the ECM obtained from murine EngelbrethÀHolmÀSwarm tumor cell lines gel were transplanted under the bilateral kidney capsule spaces, they resulted in a liver tissue formation that possessed active regeneration potential [171,172]. In a more recent study, 3D liver organoids comprised of hepatocytes and nonparenchymal cells (sinusoidal endothelial cells and hepatic stellate cells) were transplanted under kidney capsule and showed enhanced hepatic functions and survival for 8 weeks after transplantation [173].…”
Section: Sites Of Cell Transplantationmentioning
confidence: 99%
“…When hepatocytes mixed in the ECM obtained from murine EngelbrethÀHolmÀSwarm tumor cell lines gel were transplanted under the bilateral kidney capsule spaces, they resulted in a liver tissue formation that possessed active regeneration potential [171,172]. In a more recent study, 3D liver organoids comprised of hepatocytes and nonparenchymal cells (sinusoidal endothelial cells and hepatic stellate cells) were transplanted under kidney capsule and showed enhanced hepatic functions and survival for 8 weeks after transplantation [173].…”
Section: Sites Of Cell Transplantationmentioning
confidence: 99%
“…A coculture model of alveolar epithelial cells with monocyte-derived macrophages and dendritic cells, for example, has been used to model alveolar epithelial barriers to microorganisms [19]. Expansion of cocultures through the use of structurally distinct 3D organotypic systems [20, 21] is another area of intense research gaining popularity. These systems utilize free flowing media and complex scaffolds in radial-flow or rotating wall bioreactors.…”
Section: Epithelial Cell Monoculture For Modelling Diseasementioning
confidence: 99%
“…These systems utilize free flowing media and complex scaffolds in radial-flow or rotating wall bioreactors. This approach more closely replicates in vivo biology beyond basic coculturing of different cell types with rearrangement of cells into proto-organic structures [20, 21]. Moreover, recent data indicate that these systems offer new ways to study signalling events and drug interactions [21].…”
Section: Epithelial Cell Monoculture For Modelling Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…These engineered structures were viable for 3 weeks [Linke et al, 2007]. Using a biodegradable apatite-fiber scaffold, Saito et al [2011] reported the generation of the liver organoid reconstructed by mouse-immortalized hepatocytes and nonparenchymal cells (sinusoidal endothelial cells and hepatic stellate cells) in a radial-flow bioreactor. After transplantation, the organoid that had a liver-like structure with high-density layers of hepatocytes and vessel-like structures successfully survived in the omentum and kidney of recipient mice.…”
Section: Concluding Remarks: Towards the Development Of A Bioengineermentioning
confidence: 99%